PENGARUH PEMBERIAN NUTRISI YANG BERBEDA TERHADAP TANAMAN PAKCOY (Brassica rapa L) DENGAN MENGGUNAKAN SISTEM HIDROPONIK - Suryanti Sabneno; Nur Aini Bunyani; Abdonia W. Finmeta (Adisam Publisher, 2025)
Brassica rapa Latau plant commonly called mustard greens is a type of leafy vegetable classified as mustard greens. Currently, it is one of the favorite vegetables in Indonesia besides mustard greens and lettuce. Hydroponics is one of the simple farming methods. This research was conducted from March to May at the Teachers Union University 1945 NTT Green House Faculty Of Mathematics and Natural Sciences with the aim of determining the effect of nutrients (AB Mix, Growmore, Gandasil D) on the growth and yield of plants (Brassica rapa L.) in a hydroponic system, determining the best nutrients to increase the growth and yield of Brassica rapa L. plants, and determining the differences in the quality of Brassica rapa L. plant yields with different nutrient treatments.The method used to analyze the data using a Non-Factorial Complete Random Design, consisting of Three treatments repeated three times: Treatment of AB Mix, Growmore, Gandasil nutrition with the notation (A) consisting of n of three treatment levels. AO -1100-1600 ppm AB Mix (control), A1-1100-1600 ppm Growmore, A2-1100-1600 ppm Gandasil DThe results of this study indicate that the provision of Growmore, Gandasil D nutrients to bok choy plants grown hydroponically still cannot replace AB Mix nutrients. The provision of AB Mix nutrients has the highest growth and production in bok choy plants.